Relationship of anemia with clinicolaboratory measures of inflammation activity in patients with rheumatoid arthritis - A E Sizikov; E L Gelfgat; L P Konenkova; O A Gertsog; A E Sulutyan; V S Kozevnikov; E. V. Menyaeva; V A Koslov (Научно-практическая ревматология, 2007)
Objective. To study relationship of anemic syndrome with inflammation activity measures in pts with rheumatoid arthritis (RA). Material and methods. 177 pts with RA fulfilled 1987 ACR criteria were included. 132 from them had anemia at the examination. Results were processed with complex of descriptive, structural and multivariate statistics. Results. Close relationship of RA clinical features with erythropoiesis disturbances clinically manifesting with anemia development was proved. Critical hemoglobin level (<113 g/1) was determined at which pathological processes in erythron leading to the development of anemia begin significantly influence severity of immunopathological rheumatoid process. Diapasons of disease activity measures were revealed associated with anemia presence or absence in pts with RA. Diagnostic value of studied measures diapasons for prognosis of anemia development in RA was determined. Conclusion. The results of the study allow developing criteria for prognosis of anemia appearance in RA pts with normal blood concentration of hemoglobin. Such method could help to reveal early disturbances of erythron and improve RA treatment schemes with erythropoiesis modulating drugs.